Cysteinyl Leukotriene Antagonism Inhibits Bronchoconstriction in Respose to Hypertonic Saline Inhalation in Asthma - Kazani, Shamsah (2010)
BACKGROUND: In asthma, cysteinyl leukotrienes (CysLTs) play varying roles in the bronchomotor response to multiple provocative stimuli. The contribution of CysLTs on the airway's response to hypertonic saline (HS) inhalation in asthma is unknown. Whether polymorphisms in the leukotriene biosynthetic pathway affect the contribution of CysLTs to this response is also unknown. METHODS: In a prospective, randomized, double blind, placebo-controlled cross-over study, mild and moderate asymptomatic asthmatics underwent inhaled 3% HS challenge by doubling the duration of nebulization (0.5, 1, 2, 4, and 8 min) two hours after one dose of montelukast (a CysLT receptor 1 [CysLTR1] antagonist) or placebo, and after three week courses. We examined the effect of the leukotriene C(4) synthase (LTC(4)S) polymorphism (A-444C) on the efficacy of montelukast against HS inhalation in an exploratory manner. RESULTS: In 37 subjects, two hours after administration of montelukast, the mean provocative dose of HS required to cause a 20% drop in FEV(1) (HS-PD(20)) increased by 59% (9.17 after placebo vs. 14.55 ml after montelukast, p = 0.0154). Three weeks of cysLTR1 antagonism increased the HS-PD(20) by 84% (10.97 vs. 20.21 ml, p = 0.0002). Three weeks of CysLTR1 antagonism appeared to produce greater effects on blocking bronchial hyper responsiveness (two hour vs. three week HS-PD(20) values 14.55 vs. 20.21 ml respectively, p = 0.0898). We did not observe an effect of the LTC(4)S polymorphism on the response to CysLTR1 antagonism in this cohort. CONCLUSIONS: A significant proportion of HS-induced bronchoconstriction is mediated by release of leukotrienes as evidenced by substantial acute inhibition with a CysLTR1 antagonist. There was a trend toward greater inhibition of bronchial responsiveness with three weeks of therapy as opposed to acute CysLTR1 antagonism.